Prehospital Emergency Ultrasound: A Review of Current Clinical Applications, Challenges, and Future Implications - Mazen J. El Sayed; Elie Zaghrini (Emergency Medicine International)
Imaging modalities in the prehospital setting are helpful in the evaluation and management of time-sensitive emergency conditions. Ultrasound is the main modality that has been applied by emergency medical services (EMS) providers in the field. This paper examines the clinical applications of ultrasound in the prehospital setting. Specific focus is on applications that provide essential information to guide triage and management of critical patients. Challenges of this modality are also described in terms of cost impact on EMS agencies, provider training, and skill maintenance in addition to challenges related to the technical aspect of ultrasound.